Incisional surgical site infection following cesarean section: A national retrospective cohort study. (September 2019) - Saeed, Khalid BM; Corcoran, Paul; Greene, Richard A
Abstract: Objective: To determine the rate and associated risk factors for incisional surgical site infection following cesarean section in Ireland. Study Design: This study was a retrospective population-based cohort study, conducted using the Hospital In-Patient Enquiry database (HIPE) for the period 2005–2016. All women who underwent cesarean section between 2005 and 2016 in Ireland were included. Potential risk factors for incisional surgical site infection were selected based on the existing literature and their availability within the HIPE database. The risk of incisional surgical site infection following cesarean section with exact Poisson 95% confidence intervals were reported. Multivariable Poisson regression included all potential risk factors simultaneously. Risk ratios are reported with their 95% confidence intervals and P -values. Results: There were 802, 182 deliveries during the study period, 219, 859 of which (27.4%) were by cesarean section. There were 1396 cases of incisional surgical site infection, a risk of 0.63% (95% confidence interval: 0.60–0.67%). Public patients had approximately 20% higher risk and the risk was almost 40% higher among women aged over 35 years compared with those aged under 25 years. Most notable, related to the morbidities assessed, was the twofold increased risk of incisional surgical site infection associated with pre-existing diabetes and with urinary tract infection in pregnancy. Premature rupture of membranes, pyrexia during labour and postpartum haemorrhage each increased risk by 40–60%. Hematoma of a cesarean section wound remained by far the strongest risk factor for incisional surgical site infection. Conclusion: Of all the risk factors we studied, hematoma had the strongest association with development of incisional surgical site infection. Of all women birthing by cesarean section in Ireland during 2005–2016, 25% had at least one of the risk factors identified by our study. Approximately 40% of the incisional surgical site infection cases came from this 25%. This might suggest that a universal approach to reducing risk of surgical site infection is warranted.